Dense amnesia in the monkey after transection of fornix, amygdala and anterior temporal stem. - Gaffan, D; Parker, A; Easton, A (2001)
The traditional explanation of dense amnesia after medial temporal lesions is that the amnesia is caused by damage to the hippocampus and related structures. An alternative view is that dense amnesia after medial temporal lesions is caused by the interruption of afferents to the temporal cortex from the basal forebrain. These afferents travel to the temporal cortex through three pathways, namely the anterior temporal stem, the amygdala and the fornix-fimbria, and all these three pathways are damaged in dense medial temporal amnesia. In four experiments using different memory tasks, we tested the effects on memory of sectioning some or all of these three pathways in macaque monkeys. In a test of scene-specific memory for objects, which is analogous in some ways to human episodic memory, section of fornix alone, or section of amygdala and anterior temporal stem sparing the fornix, each produced a significant but mild impairment. When fornix section was added to the section of anterior temporal stem and amygdala in this task, however, a very severe impairment resulted. In an object recognition memory task (delayed matching-to-sample) a severe impairment was seen after section of anterior temporal stem and amygdala alone, with or without the addition of fornix section; this impairment was significantly more severe than that which was seen in the same task after amygdalectomy leaving the temporal stem intact, with or without fornix section. Animals with combined section of anterior temporal stem, amygdala and fornix were also impaired in object-reward association learning. However, the retention of pre-operatively acquired object-reward associations was at a high level. These results show that the pattern of impairments after section of anterior temporal stem, amygdala and fornix in the monkey, leaving hippocampus intact, resembles human dense amnesia and is different from the effects of hippocampal lesions in the monkey.